DERADICALIZING RELIGIOUS EXTREMISM LINGUISTICALLY: AN INTERTEXTUAL APPROACH TO ISLAMIC EXTREMISTS’ VIEW ON THE QUR’ANIC INTERPRETATION - Ninsiana, Widhiya (AKADEMIKA: Jurnal Pemikiran Islam, 2020)
This article is a qualitative-descriptive study which employs which concern the existing phenomenon underlying in the translation of Qur'anic verses that are generally interpreted as a means for legitimizing the acts of terrorism by radical Islamists. The integration on the linguistic knowledge of Islamic texts has been studied as a process of incorporating new information into the existing knowledge with an interdisciplinary approach. The importance of language in the multitude of learning and the discipline of science has led to its status as a condition for correct understanding of the Qur'anic messages. This study used Fairclough’s intertextual approach on the potentially abused Qur’anic verses for violence acts in the name of Islam by extremist groups such ISIS. Two patterns of understanding Islamic texts become the spectrum of how the teachings of Islam are fairly understood. Linguistic provides general criticism toward the radicals’ interpretations in understanding the Islamic sources (primarily the Qur’anic verses). Then the study ends up with an argument that the radicalism in many groups in Islam is connected with the reality of Islamic sources which essentially needs to be interpreted in the context of Islamic societies and requires dynamic reading and prospective production on the meanings of a sacred text. Keywords: intertextuality, language, and radicalism